Multimodal Regulation of NET Formation in Pregnancy: Progesterone Antagonizes the Pro-NETotic Effect of Estrogen and G-CSF - Giaglis, Stavros; Stoikou, Maria; Sur Chowdhury, Chanchal; Schaefer, Guenther; Grimolizzi, Franco; Rossi, Simona W.; Hoesli, Irene Mathilde; Lapaire, Olav; Hasler, Paul; Hahn, Sinuhe (Frontiers in Immunology, 2016)
Human pregnancy is associated with a mild pro-inflammatory state, characterized by circulatory neutrophil activation. In order to explore the mechanism underlying this alteration, we examined NETosis during normal gestation. Our data indicate that neutrophils exhibit a pro-NETotic state, modulated in a multi-modal manner during pregnancy. In general, circulatory G-CSF, the levels of which increase during gestation, promotes NET formation. Early in pregnancy, NETosis is enhanced by chorionic gonadotropin, whereas towards term is stimulated by estrogen. A complex interaction between estrogen and progesterone arises, wherein progesterone restrains the NETotic process. In this state, extensive histone citrullination is evident, yet full NETosis is inhibited. This coincides with the inability of neutrophil elastase to translocate from the cytoplasm to the nucleus, and is regulated by progesterone. Our findings provide new insight concerning gestational and hormone-driven pathologies, since neutrophil recruitment, activation and NET release could be associated with excessive endothelial and placental injury.